Nuclear Receptors as Targets for Drug Development: Peroxisome Proliferator-Activated Receptor γ in Mast Cells: Its Roles in Proliferation and Differentiation - Kazutaka Maeyama; Maiko Emi; Masashi Tachibana (Elsevier, 2005)
Mast cells are derived from stem cells in bone marrow and their proliferation and differentiation are regulated by stimulation of stem cell factor derived from fibroblasts and/or IL-3 from T lymphocytes. The peroxisome proliferator-activated receptors (PPARs) are members of the nuclear hormone receptor superfamily and ligand-activated transcription factors. It has been reported that PPARγ is expressed in mast cells, but its roles remain uncertain. Since mast cells produce and release prostaglandin D2, which is metabolized to 15-deoxy-Δ12,14-prostaglandin J2, a candidate for the endogenous PPARγ agonist, mast cells play roles in inflammation and immunological response via the PPARγ pathway. We will mainly discuss the contribution of PPARγ to the proliferation and functions in murine cultured bone marrow derived mast cells. Keywords:: peroxisome proliferator-activated receptor (PPAR) γ, mast cell, histamine, proliferation, differentiation